Debt and Economic Growth in an Oil Rich Economy: Evidence from Saudi Arabia - Muye, Ibrahim Muhammad; Kaita, Rayyan Abdulkareem; Hassan, Ahmad Fahmi Sheikh (International Journal of Economics and Financial Issues, 2017)
The objective of this paper is to examine the impact of debt on economic growth in Saudi Arabia based on autoregressive distributed lags (ARDL) approach for the period of 1969–2013. The result indicates that variables are cointegrated and null hypothesis was rejected at the 5% significance level. The coefficients of long-run result reveal that public debt affects economic growth in a positive and statistically significant manner. Furthermore, inflation was found to also enhance economic growth in the oil rich kingdom. Despite the overwhelming evidence in the literature suggesting debt stifles growth, our study recommend that policymakers maintain the current level of debt-to-GDP in the country. Keywords: Public debt, Economic Growth, Inflation, ARDL JEL Classifications: H61, H62, H63